You are the everything - Rivers, Karen, 1970- (2018)
When sixteen-year-old Elyse Schmidt and her crush, Josh Harris, are the sole survivors of a plane crash, she believes that everything is perfect and their love story is meant to be, but she finds that fate is not always what you expect it to be
Keywords: Fate and fatalism -- Juvenile fiction; Aircraft accidents -- Juvenile fiction; Survival -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Romance fiction; Novels; Young adult fiction; Fiction; Juvenile works; Novels; Romance fiction; Young adult works